2012
DOI: 10.1029/2012jd018158
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in convective storm activity over contiguous North China during the warm season based on radar mosaic climatology

Abstract: Diurnal variations in the formation and development of convective storms over contiguous North China during the warm season were studied using reflectivity from six China Next Generation Weather Radars between 2008 and 2011. Our results, including temporal and spatial analysis of hourly storm frequency through the warm season, and inter‐month comparisons during June, July and August, indicate that most storms initiate over the northwestern mountains in the afternoon as a result of solar heating, with the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 69 publications
(94 reference statements)
5
69
0
Order By: Relevance
“…This likely explains why the CI cases over the oceans moved relatively faster. Chen et al (2012) showed that storms tended to propagate from the mountains to the plains. In this study, initiated cells generally moved in a northeastward direction.…”
Section: General Resultsmentioning
confidence: 98%
“…This likely explains why the CI cases over the oceans moved relatively faster. Chen et al (2012) showed that storms tended to propagate from the mountains to the plains. In this study, initiated cells generally moved in a northeastward direction.…”
Section: General Resultsmentioning
confidence: 98%
“…Many factors can affect the locations of thunderstorms' initiation, termination, split, and merger, such as the dry line from western Oklahoma northward through western Kansas over the Great Plains in this study area [36] and topographic effects [26,37]. In this study, the relationships between thunderstorm track, initiation, termination, split, merger density and seven major land cover types are examined quantitatively ( Table 1).…”
Section: Relationship Between Thunderstorm Occurrences and Land Covermentioning
confidence: 99%
“…The IEM interpolates the base reflectivity to a 1 km grid every 5 min, and the archived datasets can be accessed via the IEM Geographic Information System (GIS) data service in PNG or GeoTIFF format. Precipitation can be estimated from radar returns based on a Z-R relationship, and the radar reflectivity data have been applied to a number of different applications including storm identification and nowcasting [25], climatology [26,27], and urbanization impacts on precipitation [28,29].…”
Section: Radar Reflectivity Datamentioning
confidence: 99%
“…The analyzed parameters include  High-resolution maps of annual average precipitation and frequency of precipitation rate (Fairman et al, 2015)  Exceedance probability of 1h rainfall (Overeem et al, 2009)  Relative frequency of severe weather as a function of time of day (Brimelow et al, 2014)  Hovmöller diagram of > 40 dBZ (longitunal average) (Chen et al, 2012)  Distribution by numbers of significant tornado events for convective mode by season (Grams et al, 2012)  Number of hail days detected in the period (Lukach et al, 2017  Hourly radar-derived hail frequency (normalized) for the entire domain and six sub-regions in the Alps. (Nisi et al 2015)  Distribution of the GEV parameters derived from satellite (HRC and CHRC) and radar datasets.…”
Section: Examples Of Data Usementioning
confidence: 99%
“…This serves the baseline information to develop accepted guidelines and standards, with a view on the rather limited lifetimes of radar systems being shorter than those of stations and the characteristic climate time scale of 30yrs. Therefore it is essential to keep not only the metadata describing the latest hardware and processing, but also a history of important hardware changes such as from nonDoppler to Doppler radars to allow for a full retrieval of the essential information also decades after the measurements had been taken and to avoid false interpretations of apparent trends which come from changes in equipment, not changes in climate.The phenomena to be monitored with weather radars include in addition to precipitation also severe mesoscale phenomena such as hailstorms and tornadoes e.g., Becker 2013, Brimelow 2004,Chen 2012, Grams 2012, Lukach 2017, Nisi 2015, Punge 2016 The central parameter is horizontal reflectivity, ZH, which is basis of precipitation estimates. The other key parameters have importance for improving the quality of precipitation estimates and as independent variables for process and climate studies.…”
mentioning
confidence: 99%